RELATIONSHIP OF MOTHER'S KNOWLEDGE ABOUT DENTAL HEALTH MAINTENANCE WITH CARIES STATUS IN AL-HIKMAH KIDS OF JAMBI CITY IN 2018 - Sukarsih Sukarsih; Aida Silfia; Sri Febrianti (Poltekkes Kemenkes Jambi, 2018)
Mother's knowledge about dental health will greatly determine health status of her child's teeth later. Mothers have an important role in their family, as a wife and as a mother. The first figure that is known to the child as soon as he is born is the mother, therefore mother’s behavior and habits can be emulated by child. In the other side, knowledge is not enough to detrmine child dental health, it needs to be followed by commendable attitudes and actions. The Australian dental association has revealed that: